THE ENLARGEMENT OF THE EUROPEAN UNION AND THE (NON) MEMBERSHIP OF TURKEY - Pukenis, Robertas (European Scientific Journal, ESJ, 2014)
The first chapter of the present article gives analysis of the causes of the development of the EU and the conditions for entry of new candidate states; the second chapter tackles upon the situation in the membership negotiations between Turkey and the EU; the article ends with conclusions and the bibliography. The state willing to get entry into the EU should have a democratic system of government. Before entry, the candidate state has to conduct negotiations in 35 sections, covering all spheres of political, economical, public and legal life. The country is accepted in the Union when it concludes the negotiations in all 35 sections with unanimous approval of all member states of the EU. A certain level of the maturity of the candidate state is needed: harmonization of the national laws with the legislative basis of the EU; proper economic development; and respect for basic human values and rights. The terms and conditions are the same for all candidates. Road of Turkey to the European Union has been rough and complicated up to now. This country is eager to collaborate with the EU (and it does that) and willing to comply with European standards and norms of public life. The negotiations have been going on with fits and starts; there is evident progress in the economy of Turkey, but the country lags behind in protecting human rights. Other obstacles impeding the course of negotiations are occupation of Cyprus and pending issue of the Kurds. External obstacles to Turkish membership are associated with negative approach of some European leaders and fears of the citizens. Nevertheless, recent course of events gives valid hope that sooner or later Turkey will get a membership card to the European Union. One has every reason to think that in a global world liberal democratic system is more appealing and more profitable to every nation and they are to seek for prosperity by shared efforts.